Tahfidzul Al-Qur’an Dalam Peningkatan Karakter Religius Siswa Di MTs Negeri Kota Pasuruan - Mokh. Zainur Ramadhani; Zakaria Zakaria (Ta'limDiniyah: Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2023)
This research describes how the tahfidz Al-Qur'an program is implemented to strengthen the religious character of students at the State Madrasah Tsanawiyah Pasuruan City. The research method used is a case study which involves collecting data through observation, interviews and document analysis. The research results show that the tahfidz Al-Qur'an program plays a significant role in increasing students' understanding of Islamic religious teachings and forming strong religious character. Students who take part in this program experience improvements in aspects such as piety, discipline, responsibility and noble morals. The implications of the research show that tahfidz Al-Qur'an can be an effective tool in developing the religious character of students at MTS Negeri Pasuruan City and similar schools